Ryzyko kredytowania małych i średnich przedsiębiorstw w Polsce - Grzywacz, Jacek (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
The SME sector is a main stimulus of the economic development in Poland. The valid problems in this sector concern both aspects as leading the current business activity as well as a trouble keeping of the financial liquidity. Therefore the access to credit is conditioning the real opportunities of functioning on the market and its development today. However the cost of a bank loan in Poland effectively is still suppressing the investment enthusiasm of entrepreneurs. This cost, from bank point of view, is an outcome of the rigorous evaluation of the credit risk in activity of the small and medium enterprise sector.